Chemical composition and in vitro biological activities of cardoon (Cynara cardunculus L. var. altilis DC.) seeds as influenced by viability: Chemical prospection and bioactivity of cardoon seeds - Mandim, Filipa (2018)
Cardoon is a multi-purpose crop for several industries. In this study, cardoon seeds were separated according to the viability and characterized for their chemical composition and bioactivities. Viable seeds contained higher levels of α-tocopherol (6.7 mg/100 g), lipids (23.11 g/100 g, manly oleic and linoleic acids), and free sugars (5.4 g/100 g) than the unviable ones. The hydroethanolic extract of viable seeds presented a higher concentration of phenolic compounds, namely 5-O-caffeoylquinic (8.0 mg/g) and 3,5-O-dicaffeoylquinic (43.9 mg/ g) acids, and greater in vitro antioxidant activity. Both extracts showed antibacterial properties, but the best results were achieved with unviable seeds. The extracts had similar antifungal activity but did not reveal antiinflammatory capacity or cytotoxicity to the tested cell lines. Therefore, while viable seeds contained antioxidant phytochemicals and an energy and carbon source for germination, unavailable seeds stood out for their potential to be used in the development of bio-based antibacterial ingredients.